Development of an expanded‐field irradiation technique using a gimbaled x‐ray head. Issue 10 (24th September 2014) - Ono, Tomohiro; Miyabe, Yuki; Yamada, Masahiro; Yokota, Kenji; Kaneko, Shuji; Sawada, Akira; Monzen, Hajime; Mizowaki, Takashi; Kokubo, Masaki; Hiraoka, Masahiro
Abstract : Purpose: : The Vero4DRT has a maximum field size of 150.0 × 150.0 mm. The purpose of the present study was to develop expanded‐field irradiation techniques using the unique gimbaled x‐ray head of the Vero4DRT and to evaluate the dosimetric characteristics thereof. Methods: : Two techniques were developed. One features gimbal swing irradiation and multiple static segments consisting of four separate fields exhibiting 2.39° gimbal rotation around two orthogonal axes. The central beam axis for each piecewise‐field is shifted 40 mm from the isocenters of the left–right (LR) and superior–inferior (SI) directions, and, thus, the irradiation field size is expanded to 230.8 × 230.8 mm. Adjacent regions were created at the isocenter (a center‐adjacent expandedfield) and 20 mm from the isocenter (an off‐adjacent expandedfield). The field gaps or overlaps of combined piecewise‐fields were established by adjustment of gimbal rotation and movement of the multileaf collimator (MLC). Another technique features dynamic segment irradiation in which the beam is delivered while rotating the gimbal. The dose profile is controlled by a combination of gimbal swing motion and opening and closing of the MLC. This enabled the authors to expand the irradiation field on the LR axis because the direction of MLC motion is parallel to that axis. A field 220.6 × 150.0 mm in dimensions was configured and examined. To evaluate the dosimetric characteristics of the expandedfields, films inserted into water‐equivalent phantoms at depths of 50, 100, and 150 mm were irradiated and field sizes, penumbrae, flatness, and symmetry analyzed. In addition, the expanded‐field irradiation techniques were applied to intensity‐modulated radiation therapy (IMRT). A head‐and‐neck IMRT field, created using a conventional Linac (the Varian Clinac iX), was reproduced employing an expanded‐field of the Vero4DRT. The simulated dose distribution for the expanded‐IMRT field was compared to the measured dose distribution. Results: : The field sizes, penumbrae, flatness, and symmetry of the center‐ and off‐adjacent expanded‐fields were 230.2–232.1 mm, 6.8–10.7 mm, 2.3%–5.1%, and −0.5% to −0.4%, respectively, at a depth of 100 mm. Similarly, the field sizes, penumbrae, flatness, and symmetry of dynamic segment irradiation on the LR axis were 219.2 mm, 6.0–6.2 mm, 3.4%, and −0.1%, respectively, at a depth of 100 mm. In the area of expanded‐IMRT dose distribution, the passing rate of 5% dose difference was 85.8% between measurements and simulation, and the 3%/3 mm gamma passing rate was 96.4%. Conclusions: : Expanded‐field irradiation techniques were developed using a gimbaled x‐ray head. The techniques effectively extend target areas, as required when whole‐breast irradiation or head‐and‐neck IMRT is contemplated.